Enhancing Literacy and Character Building among Bupolo Millennials: Strategies and Impact of the Community Learning House on Buru Island - Harziko, Harziko; Ami, Iin Sulastri Ode; Alimin, La Ode; Susiati; Umasugi, Selfa Yanti (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
Revitalizing literacy among millennials, particularly those in remote regions like Buru Island, necessitates collaborative efforts from government bodies, literacy communities, and families. The Bupolo millennials face significant challenges in accessing quality reading materials. The establishment of the Community Learning House (RBK) on Buru Island aims to address these challenges by fostering a literacy culture. This study identifies effective strategies to enhance literacy and build character among Bupolo millennials through RBK. Using a descriptive qualitative approach with phenomenological methods, data were collected via participatory observation, semi-structured interviews, and documentation at RBK, Buru Island. Findings reveal nine key strategies: Oral Tradition Literacy, Media Literacy, Basic Literacy, Literacy Tourism with Coastal Children, Literacy Carnival, Literacy Enters Village, Mountaineering Literacy, School Literacy, and Sharing Literacy. These strategies cultivate qualities such as curiosity, honesty, tolerance, creativity, hard work, independence, cultural appreciation, nationalism, and social responsibility among Bupolo millennials.